Association between multiple geriatric syndromes and life satisfaction in community-dwelling older adults: A nationwide study in Taiwan. Issue 3 (May 2015) - Yang, Deng-Chi; Lee, Jenq-Daw; Huang, Chi-Chang; Shih, Hsin-I.; Chang, Chia-Ming
Highlights We investigated life satisfaction in community-dwelling older adults. Demographic factors and geriatric syndromes were associated with life satisfaction. Life satisfaction was not affected in the elderly with only 1 geriatric syndrome. Increased number of geriatric syndromes were associated with lower life satisfaction.